The Impact Of Active Learning Strategies On Education And Learning Achievements/ استراتيجيات التعلّم النشط وأثرها في عملية التعليم والتحصيل الدراسي - Alkasem, Ahmad Abdulrahman; Mohamed, Yuslina (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The world is undergoing rapid progress, leading to a significant knowledge revolution. This revolution has brought numerous technical and educational developments in educational institutions to improve learning through modern teaching strategies. The concept of